Elchtest. Die Reform des staatlichen Eisenbahnsystems in Schweden. - Schöller, Oliver; Borcherding, Anke (Deutscher Verkehrs-Verlag, 2004)
Auf der Suche nach Reformstrategien für das deutsche Eisenbahnwesen wird der Blick immer wieder in Richtung Skandinavien gerichtet. Insbesondere Schweden gilt vielen bis heute als Musterbeispiel eines erfolgreich beschrittenen Reformwegs. Der Beitrag unternimmt eine differenzierte Bestandsaufnahme des langjährigen schwedischen Reformprozesses. difu

The insolvency procedures initiated for Sweden's rail carrier at the end of 2002 and the appointment of a fact-finding commission - whose recommendations for a future railway policy were published at year's end - were seen as a turning point in the context of the rail sector's future policy. This report summarizes the situation and questions to what extent the results of the long term reform policy 'step by step' - which gave the Swedish government a far-reaching role as a moderator - can serve as an acceptable alternative to the negative aspects associated with Britain's rail system. Highlights show the economic, social and ecological effects associated with rail reforms in relation to a comprehensively sustainable concept. The controversial reform process resulting from this, proves to be different from the British system although, increasingly, similar features emerge. difu
Keywords: Schienenverkehr; Öffentlicher Verkehr; ÖPNV; Eisenbahn; Regionalisierung; Privatisierung; Verkehrsinfrastruktur; Ökologie; Nachhaltigkeit; Ökonomie; Bahnsystem; Reformprozess